Analisa Pengaruh Konfigurasi Pipa Pemanas Air Surya Terhadap Efisiensi - Darwin, Darwin (ROTOR, 2013)
In order to reduce or replace the use of wood fuel, oil and natural gas to heat water, has a lot of research being done to find alternative energy sources. Solar energy is one alternative energy that can be used to heat water. Solar collector is a device that serves to collect the incoming solar energy and convert it into heat energy which in turn forwarded to the working fluid. The purpose of this study solar water heater is to compare the influence of the configuration of pipes and pipe parallel series with the addition of the collector absorber plate honeycomb shaped the performance of solar energy water heater so that in can be efficiency. From research result obtained temperature irrigate in parallel pipe collector tank at angle 5o equal to 52 oC and also reached efficiency that is 46,16 %, at angle 10o equal to 54 °C reached efficiency 48,15 %, at angle 15o equal to 51 oC reached efficiency 45,10 % and at angle 20o equal to 48 °C and also reached efficiency that is 39,60 % while the water temperature inside the tank to the collector pipe series at angle 5 o equal to 48 oC reached efficiency is 41.67 %, the angle at 10 o equal to 49 oC reached efficiency is 42.86 %, angle 15 º equal to 47 °C reached efficiency is 40.43 % and at an angle 20o equal to 46 °C and also reached efficiency that is 39,14 %. In general, the obtained results indicate that the solar collector with parallel pipe configuration has better efficiency compared to solar collector with series pipe configuration. Keywords: Solar Energy, Solar Collectors, Series Pipe, Parallel Pipe, Efficiency